Using Animation Video to Enhance EFL Students' Listening Comprehension - Muhammad Ibrahim Insan Al Hakim (Retain: Journal of Research in English Language Teaching, 2024)
Animation video is a type contemporary entertainment that blends speech, music, and visuals with moving pictures. The purpose of this study is to determine whether or not students’ listening comprehension significantly improves after receiving instruction via animated videos. This research employed a quantitative methodology. The Visual Communication Design Major (DKV) was chosen as the subject of this research at one state vocational highschool in Surabaya. Class 10 DKV 1 served as the experimental group, and class 10 DKV 2 as the control group in this research.The study’s findings indicate a substantial difference in post-test results between the experimental and control groups, indicating that the experimental group’s pupils had much higher listening comprehension than the control group’s. Thus, it can be said that using animated videos about describing person and describing things as an instructional tool at the treatment stage is very effective in improving the experimental group’s pupils’ listening comprehension in this present research.